2010
DOI: 10.1029/2010gl042648
|View full text |Cite
|
Sign up to set email alerts
|

Cluster observations of EMIC triggered emissions in association with Pc1 waves near Earth's plasmapause

Abstract: [1] The Cluster spacecraft were favorably positioned on the nightside near the equatorial plasmapause of Earth at L ∼ 4.3 on 30 March 2002 to observe electromagnetic ion cyclotron (EMIC) rising tone emissions in association with Pc1 waves at 1.5 Hz. The EMIC rising tone emissions were found to be left-hand, circularly polarized, dispersive, and propagating away from the equator. Their burstiness and dispersion of ∼30s/Hz rising out of the 1.5 Hz Pc1 waves are consistent with their identification as EMIC trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
161
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(183 citation statements)
references
References 33 publications
21
161
1
Order By: Relevance
“…Although EMIC waves have been intensively investigated [e.g, Kennel and Petschek, 1966;Young et al, 1981;Rauch and Roux, 1982;Roux et al, 1982;Anderson et al, 1996;Fraser and Nguyen, 2001;Halford et al, 2010;Pickett et al, 2010;Zhang et al, 2010Zhang et al, , 2011Min et al, 2012;Allen et al, 2013;Lin et al, 2014], plasma properties relevant to EMIC wave excitation have not been fully understood in the magnetosphere due to the wide spatial extent of EMIC wave generation and propagation. For example, Lin et al [2014] recently found that the correlation of positive A hp events, EMIC instability threshold (Σ h > S h ), and EMIC waves observed by the polar-orbiting Cluster spacecraft is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EMIC waves have been intensively investigated [e.g, Kennel and Petschek, 1966;Young et al, 1981;Rauch and Roux, 1982;Roux et al, 1982;Anderson et al, 1996;Fraser and Nguyen, 2001;Halford et al, 2010;Pickett et al, 2010;Zhang et al, 2010Zhang et al, , 2011Min et al, 2012;Allen et al, 2013;Lin et al, 2014], plasma properties relevant to EMIC wave excitation have not been fully understood in the magnetosphere due to the wide spatial extent of EMIC wave generation and propagation. For example, Lin et al [2014] recently found that the correlation of positive A hp events, EMIC instability threshold (Σ h > S h ), and EMIC waves observed by the polar-orbiting Cluster spacecraft is low.…”
Section: Discussionmentioning
confidence: 99%
“…EMIC waves are preferentially generated in regions where hot anisotropic H + and cold dense ion populations spatially overlap [e.g., Jordanova et al, 2001;Pickett et al, 2010;Zhang et al, 2011]. In the terrestrial magnetosphere, these ion populations can commonly be found where the ring current overlaps the plasmasphere or plasmaspheric plumes [Gurgiolo et al, 2005;Thorne, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…EMIC waves can cause rapid scattering and loss for ring current ions (Jordanova et al 2001b) and relativistic electrons above 0.5 MeV (Thorne and Kennel 1971;Lyons and Thorne 1973;Albert 2003;Summers and Thorne 2003;Meredith et al 2003b). Favored regions for EMIC excitation include the overlap between the ring current and the plasmasphere (Pickett et al 2010), dayside drainage plumes (Morley et al 2009), and the outer dayside magnetosphere in association with solar wind pressure fluctuations (Arnoldy et al 2005;Usanova et al 2008;McCollough et al 2009). Theoretical global modeling of EMIC wave excitation has confirmed the plasmapause and plume as favored regions of cyclotron resonant instability (Jordanova et al 2007;Chen et al 2010a) and demonstrated that the wave excitation can also be enhanced by density fluctuations within a plume (Chen et al 2009a).…”
Section: Fig 2 Spectrogram Of Waves Observed On Combined Release Andmentioning
confidence: 99%
“…We still neglect the contributions of H + -and O + -mode EMIC waves in this study because He + -mode of EMIC waves is a dominant mode observed in the inner magnetosphere. We also do not consider the so-called EMIC rising tone emissions although they are observed in a close association with the Pc1 waves [Pickett et al, 2010]. There are two reasons why we do not include the EMIC rising tone emissions in our model at this point.…”
Section: Introductionmentioning
confidence: 99%